The motivation of university students in speaking English on extracurricular activity: Extrinsic or intrinsic? - Mawardin Muhammad Said; Ferry Rita; Sriati Usman (JOALL (Journal of Applied Linguistics and Literature), 2023)
Research on motivation of students in speaking English on extracurricular activity has been really conducted but students are still afraid of speaking English.. This manuscript is a research result dealing with motivation of English Education students in Department of Language and Art Education at Faculty of Teacher Training and Education, Tadulako University in speaking English on extracurricular activity. English speaking skill should be developed on extracurricular activity to make ideal atmosphere, but that activity has not been effective yet on all study programs except English Education at that faculty, so that the students have not been able to speak English yet. This research aims at identifying what motivates the university students and how their intention is. Its target is they taste different academic athmosphere to have English skill to interact with English speakers. Respondents of the research were 25 English education students. Its data were collected through Identification (as a procedure) by using Questionnaire (as an instrument) then analysed by using Descriptive Method. The university students join it to be able to communicate in English and get certificate. Those are extrinsic moivation and intrinsic one. Most of them were selfmotivated, so their intrinsic motivations were greater than their extrinsic one. Motivation by themselves or selfmotivator is the greatest. This implies to support decision making in developing English speaking skill of university students. They hopefully carry out and join extracurricular activities to practice their English orally for having English speaking skill proficiently.